Digital Literacy and Distributive Justice: Key Issues in ZISWAF Management in South Sulawesi - Muhammad Syujai (POKJANAS PERENCANA KEMENTERIAN AGAMA RI, 2025)
This policy paper describes that management of Islamic philanthropy, including zakat, infaq, sadaqah, and waqaf (ZISWAF), in South Sulawesi has great potential to reduce poverty and economic inequality; however, its implementation has not yet yielded the best results. The adoption of digital platforms for donations is still low, with most contributions being made through conventional means. This article identifies three main issues that hinder the use of digital ZISWAF in the region: low digital literacy and public trust, limited regulation and inter-agency coordination, and inadequate technological innovation. These issues are interconnected: low digital literacy makes the public hesitant to use digital platforms, while cases of online fraud further erode trust. Furthermore, the lack of specific internal regulations from the Regional Office of the Ministry of Religious Affairs of South Sulawesi has caused digitalization initiatives to be slow and unstructured. Using the USG (Urgency, Seriousness, Growth) analysis method, it was found that the problem of low digital literacy and public trust is the top priority that must be addressed immediately. The proposed solution is to issue a Decree of the Director General of Islamic Community Guidance regarding the Integration of the Digital Philanthropy Literacy Curriculum into Religious Programs. This article analyzes the problem from various theoretical perspectives, including Social Capital Theory (Putnam, 2000), Diffusion of Innovation Theory (Rogers, 2003), Institutional Theory (Scott, 2008), and Distributive Justice Theory (Rawls, 1999). Relevant conceptual and regulatory support is also used to strengthen the argument, affirming that the Ministry of Religious Affairs has a central role as a regulator and facilitator to build a trusted and sustainable digital Islamic philanthropy ecosystem.